2015
DOI: 10.22458/urj.v7i1.863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, intensity and abundance of endoparasites in Oreochromis niloticus and Tilapia zilli (Pisces: Cichlidae) from Asa Dam, Ilorin, Nigeria

Abstract: ABSTRACT:Disease is an important factor in fisheries, affecting both wild and cultured species. Using standard parasitological techniques we determined the prevalence, mean intensity and abundance of endoparasites from 250 specimens of two cichlids, Oreochromis niloticus and Tilapia zilli from Asa dam, Ilorin, North Central Nigeria between February and August, 2013. We found two digenetic trematode parasites: Euclinostomium heterostomum and Clinostomum tilapiae. The highest prevalence was recorded in O. niloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
7
2
Order By: Relevance
“…The prevalence of gastrointestinal helminths was found to be more frequent in fishes sampled from Gombe main market (17.0%) followed by Kwadon market (15.0%) and Gombe old market (10.70%) in a descending order. Although, the prevalent rate of gastrointestinal helminths in Tilapia zilli reported in this current study was lower than the findings of Bichi and Ibrahim (2009) who recorded 53.40% in Kano, 60.23% reported by Olofintoye (2006) in Ekiti and 56.4% reported by Amaechi (2014) in Ilorin. It is however, higher than 18.70% reported by Biu and Nkechi (2013) in Maiduguri and 37.10% reported by Goselle et al (2008) in Jos.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The prevalence of gastrointestinal helminths was found to be more frequent in fishes sampled from Gombe main market (17.0%) followed by Kwadon market (15.0%) and Gombe old market (10.70%) in a descending order. Although, the prevalent rate of gastrointestinal helminths in Tilapia zilli reported in this current study was lower than the findings of Bichi and Ibrahim (2009) who recorded 53.40% in Kano, 60.23% reported by Olofintoye (2006) in Ekiti and 56.4% reported by Amaechi (2014) in Ilorin. It is however, higher than 18.70% reported by Biu and Nkechi (2013) in Maiduguri and 37.10% reported by Goselle et al (2008) in Jos.…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore, accurate identification of parasites is important so that a build-up of parasite numbers can be prevented (Goselle et al, 2008). Various researches have been conducted and have reported varying prevalent rates of gastrointestinal helminths of Tilapia species in some parts of Nigeria, 37.09% was reported by Goselle et al (2008) in Jos, Onyedineke et al (2010) reported 60.6% in Edo State, 56.4% reported by Amaechi (2014) in Ilorin, Bichi and Ibrahim (2009) reported 43.3% in Kano, 45.3% was reported by Olofintoye (2006) in Ekiti, 18.7% was reported by Biu and Nkechi (2013) in Maiduguri, Uhuo et al (2014) reported 19.8% in Eboyi State. Other researches by Oniye et al (2004) in Zaria; Akinsanya et al (2007) in Lagos State, Awharitoma and Ehigiator (2012) in Southern Nigeria and Olurin et al (2012) in Ibadan South west Nigeria are of great value.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of Cauyan that linear correlations between total parasite count and fish total length showed negative relationships for all species. It also agrees with the findings of Amaechi [1] that there was no relationship between the endoparasites and size of the fish. Khalil [15] also stated that there was no relationship between fish length and parasitism, given that larger-sized fish were less affected by infection than the smallersized fishes.…”
Section: Discussionsupporting
confidence: 92%
“…Endoparasites found at the gills, stomach and intestine of the fish during macroscopic and microscopic examination were identified, counted and photographed. The relations of the number of parasites and the fish length, fresh weight and body height were determined using Pearson Correlation Analysis [1]. The prevalence and mean intensity of the different endoparasites in the fish samples were accomplished by using the formula: It is a parasite that is 5 to 20 cm in length, kidney shaped in appearance with 2 flagella attached to the ventral part of the body.…”
Section: Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation